Confession from the Point of View of the Experience of the People Seeking Help: An Empirical Study about Confessional Practices in Finland and Hungary - Joób, Máté; Paavo, Kettunen (European Journal of Mental Health, 2013)
The article presents confession practice from the point of view of the confessants. The practice and experiences of the confessants are presented based on two earlier research studies. The source material of both researches was based on letters written by the confessants themselves with the need of stress relief. As the collection and analysis of the material was conducted with a similar method, there is also a possibility to compare the fi ndings of the two research studies. Based on letters from Finnish and Hungarian respondents, the authors look at several topics: expectations from the confessants, criteria of experiencing absolution, the relationship between confessant and confessor and the effect of confession on the spiritual life of the confessant.